EXPANDED DENGUE SYNDROME AND ATYPICAL MANIFESTATIONS - HASEEB, ABDUL; HAREESH; SHARANABASAPPA (International Journal of Current Pharmaceutical Research, 2024)
Objective: Dengue fever, once seen as a classical febrile illness, has transformed into a global concern with the emergence of Expanded Dengue Syndrome (EDS). EDS is characterized by atypical and severe manifestations affecting multiple organ systems, including the central nervous system, liver, heart, and kidneys. This syndrome challenges the traditional understanding of dengue and necessitates heightened clinical awareness, timely intervention, and comprehensive research. Co-infections further complicate the clinical landscape, emphasizing the need for accurate diagnosis and targeted therapeutic strategies. Methods: This prospective observational study was conducted at Yashoda Super Specialty Hospital, Malakpet, Hyderabad, from January 2018 to January 2021. The study aimed to identify and analyze atypical presentations of dengue fever in patients of all age groups. Inclusion criteria involved laboratory-confirmed dengue cases with atypical manifestations indicative of EDS. Data collection included comprehensive clinical, laboratory, and radiological information. Ethical considerations and statistical analysis were conducted using SPSS software. Results: The study analyzed 150 cases of EDS, encompassing atypical manifestations such as encephalopathy, myocarditis, acute liver failure, and renal impairment. CNS involvement was the most common atypical manifestation (20%), followed by myocarditis (15%) and acute liver failure (10%). Renal impairment was observed in 5% of cases. Co-infections were identified in 25% of EDS cases, further complicating clinical management. The mortality rate among EDS patients was 5%, emphasizing the importance of early recognition and aggressive organ-specific interventions. Conclusion: Expanded Dengue Syndrome challenges the conventional perception of dengue fever, highlighting atypical manifestations and co-infections. Heightened clinical awareness, a broad differential diagnosis, and aggressive management strategies are essential for addressing the multifaceted nature of EDS. Further research is needed to develop targeted interventions for this complex and evolving disease.